1993
DOI: 10.1093/oxfordjournals.aje.a116855
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Analysis of Kaposi's Sarcoma as an Early and Later AIDS Outcome in Homosexual Men

Abstract: The authors separately studied the epidemiology (risk and risk factors) of Kaposi's sarcoma occurring as an initial acquired immunodeficiency syndrome (AIDS) outcome (early Kaposi's sarcoma) and later after a different initial AIDS outcome (later Kaposi's sarcoma) in a cohort of 2,591 human immunodeficiency virus type 1-infected gay men of the Multicenter AIDS Cohort Study between 1984 and 1992. Among 844 AIDS cases, 202 presented with early Kaposi's sarcoma, 101 subsequently developed later Kaposi's sarcoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 0 publications
7
38
1
1
Order By: Relevance
“…While this finding is consistent with prior studies [6,17], ours results were limited by the fact that 78% of the study population was co-prevalent. Prior to our study, smoking had been associated with a decreased incident of both classic and AIDS-related KS [20,30]. Goedert et al [20] observed that subjects with classic KS were only 25% as likely to be current or former smokers as compared to non-KS controls.…”
mentioning
confidence: 67%
“…While this finding is consistent with prior studies [6,17], ours results were limited by the fact that 78% of the study population was co-prevalent. Prior to our study, smoking had been associated with a decreased incident of both classic and AIDS-related KS [20,30]. Goedert et al [20] observed that subjects with classic KS were only 25% as likely to be current or former smokers as compared to non-KS controls.…”
mentioning
confidence: 67%
“…In a study restricted to HHV-8 seropositives, Goedert et al 22 observed that subjects with classical KS were only 25% as likely to be current or former smokers as compared to non-KS controls. In the Multicenter AIDS Cohort Study of HIV-positive male homosexuals, Hoover et al 23 examined KS risk without regard to HHV-8 serostatus and found a 30-39% reduction in smokers. These consistent findings suggest the association is real, warranting further study to elucidate the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, AIDS report in developed countries is approximately 85% complete (Buehler et al, 1992). About one-third of KS in HIV-positive individuals develop after AIDS diagnosis (Hoover et al, 1993). Furthermore, the 1993-94 incidence is influenced by the correction for reporting delay, a procedure that is less reliable for the most recent period (Dal Maso et al, 1995).…”
Section: Discussionmentioning
confidence: 99%